Optimizing tendon repair and regeneration: how does the in vivo environment shape outcomes following rupture of a tendon such as the Achilles tendon? - Hart, David A.; Ahmed, Aisha S.; Chen, Junyu; Ackermann, Paul W. (Frontiers in Bioengineering and Biotechnology, 2024)
Risk for rupture of the Achilles tendon, and other tendons increases with age. Such injuries of tissues that function in high load environments generally are believed to heal with variable outcome. However, in many cases, the healing does not lead to a good outcome and the patient cannot return to the previous level of participation in active living activities, including sports. In the past few years, using proteomic approaches and other biological techniques, reports have appeared that identify biomarkers that are prognostic of good outcomes from healing, and others that are destined for poor outcomes using validated criteria at 1-year post injury. This review will discuss some of these recent findings and their potential implications for improving outcomes following connective tissue injuries, as well as implications for how clinical research and clinical trials may be conducted in the future where the goal is to assess the impact of specific interventions on the healing process, as well as focusing the emphasis on regeneration and not just repair.